Helen Keller. - Davidson, Margaret, 1936-; Fox, Vicki (New York Scholastic, 1969)
A biography stressing the childhood of the woman who overcame the handicaps of being blind and deaf.
H
b
b
Keywords: Keller, Helen, -- 1880-1968 -- Juvenile literature; Keller, Helen, -- 1880-1968.; Deafblind women -- Biography -- Juvenile literature; Blind; Blindness; Deaf; People with disabilities; Women -- Biography